Overview of the application status and development trends of hydropower and geothermal power in New Zealand - Yiheng Guan; Scott Post; Dan Zhao; Senlin Zhang; Sid Becker (Energy and Built Environment)
Hydropower is an early and well-developed form of electricity generation in New Zealand, as well the most important form of electricity generation globally. This paper analyses the world's energy structure, along with New Zealand's energy structure, the distribution of existing hydroelectric power plants, hydroelectric power operators, the distribution of hydroelectric grids, types of hydroelectric power stations and types of hydro turbines. Furthermore, it also compares the hydropower development in New Zealand relative to other nations, such as China and Norway. New Zealand's power plants: hydro, geothermal and wind farms, are compared in terms of environmental impact, investment benefits, levelized generation costs, Māori culture and generation technology. Because countries worldwide are acting towards the 2050 carbon neutral, the use of electric vehicles is gradually increasing. Finally, Therefore, a surge in electricity generation, and its usage, is anticipated. To overcome this issue, upgrading and expanding existing hydropower plants or building small hydropower is considered to be one of the best options for New Zealand to fulfill the electricity demand and commitment towards low carbon emission.